Incidental Umbilicolith Encountered in Laparoscopic Paraumbilical Hernia Repair Surgery-A Case Report - Ahmed, Laraib; Akhtar, Riaz; Zahra Naqvi, Syeda Wafa (Indus Journal of Bioscience Research, 2024)
Umbilicolith is derived from the Latin word "umbilicus" and "lithos,". It refers to a rare and enigmatic dermatologic condition characterized by the accumulation of sebum, keratin, and other debris and the formation of calcified concretions within the umbilical cavity. This condition is also known as an omphalolith. It is typically asymptomatic. The etiology of this entity remains largely unknown. However, it has been postulated to be associated with various factors. These are poor hygiene, infections, and chronic inflammation. Hence, in this case report, we present the case of a female patient who presented with a paraumbilical hernia. She was found to have an umbilicolith during laparoscopic hernia repair.